2014
DOI: 10.1021/jo5022635
|View full text |Cite
|
Sign up to set email alerts
|

A Twist on Facial Selectivity of Hydride Reductions of Cyclic Ketones: Twist-Boat Conformers in Cyclohexanone, Piperidone, and Tropinone Reactions

Abstract: The role of twist-boat conformers of cyclohexanones in hydride reductions was explored. The hydride reductions of a cis-2,6-disubstituted N-acylpiperidone, an N-acyltropinone, and tert-butylcyclohexanone by lithium aluminum hydride and by a bulky borohydride reagent were investigated computationally and compared to experiment. Our results indicate that in certain cases, factors such as substrate conformation, nucleophile bulkiness, and remote steric features can affect stereoselectivity in ways that are diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
1
32
0
2
Order By: Relevance
“…For solvent based calculations, a more realistic model would consist of the lithium counterion being coordinated with solvent molecules. However, previous computational work has indicated that non‐solvated models are sufficient to accurately reproduce experimentally obtained selectivity of hydride reductions …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…For solvent based calculations, a more realistic model would consist of the lithium counterion being coordinated with solvent molecules. However, previous computational work has indicated that non‐solvated models are sufficient to accurately reproduce experimentally obtained selectivity of hydride reductions …”
Section: Resultsmentioning
confidence: 98%
“…In the presence of EWG, the trans isomer is also predicted as the most stable product, while experimental data indicate that the cis isomer is obtained as the major compound. However, the stereoselectivity of hydride reductions of cyclohexanones is kinetically controlled and the ratio of reaction products is usually obtained from the Gibbs free energy of the different transition states . For the methoxy substituent, the B3LYP−D3 functional (MUE=0.15 kcal mol −1 ) reproduces the best the isomer's relative energies, outperforming the Minnesota functionals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The workup of this reaction was performed offline after the reaction mixture was completely collected in the corresponding vial. The reduction of ketone 2b was performed in batch using N ‐Selectride to give alcohol 12…”
Section: Resultsmentioning
confidence: 99%